Virtual reality as a distraction therapy in obstetrics and gynaecology. Issue 3 (14th May 2021) - Harper, Alice M; Wastnedge, Elizabeth; Sivanathan, Aparajithan; Jordan, Aileen; Harper, Samuel; Lim, Theodore; Denison, Fiona C
Abstract : Background: Virtual reality (VR) is an effective distraction therapy across a variety of healthcare settings but there is minimal research on its potential applications within obstetrics and gynaecology. Aim: To explore the acceptability and preferences for VR as distraction therapy within obstetrics and gynaecology. Methods: Questionnaires were developed and administered to seek both obstetric and gynaecology women's and staff members' opinions on VR use within clinical settings and hardware and software options. Likert scales were used to explore opinions on VR. Data were analysed by descriptive statistics. Results: 247 questionnaires were completed (90 obstetric and 157 gynaecology). On average 57% of women and 75% of staff felt positively about trialling VR within obstetric and gynaecology clinical settings. For hardware, glasses were the preferred head equipment but there were no clear preferences for image viewing. For software, 'beach' was the most popular environment and accompanying audio favoured. Women's and staff members' opinion on complete immersion was largely negative. Conclusions: There is wide acceptability for VR within obstetrics and gynaecology. Differing opinions for specific hardware and software preferences prompts consideration of clinical settings, end-users and healthcare professionals in the design of future VR technologies and clinical trials for obstetrics and gynaecology.